DESAIN DAN SIMULASI KEGAGALAN STIK MANDRIL ROKET RX-100 PADA PROSES DECORING MENGGUNAKAN SOFTWARE SOLIDWORK - Setiawan, Ahmad Yudi; Supardi, Nurul Iman; Ismah, Yulia Azatil (UNIB Press, 2024)
The substances used in rocket propellant have the ability to produce molecular gas at very high pressure and temperature during combustion. This material has great energy, and can explode so it is widely used in firearms, explosives and rockets. During the process of making rocket propellant, there is a process, namely the decorating process, which is the process of withdrawing the mandril stick from the propellant mold tube. The mandril stick is a component found at the end of the mandril itself, used as a link between the electric pulley and the mandril which is useful for pulling the mandril out of the mold tube, so that the propellant forms grains according to the mandril that has been printed in the propellant mold tube. The manufacture of mandril sticks is assisted by Solidwork software. In this research, a simulation was carried out on the mandril stick in order to determine the distribution of von Mises stress, displacement, and safety of factors on the RX-100 rocket mandril stick.